Enhancing thermoelectric performance of BiCuSeO - วงษ์ประการ, ศุภกฤต; พินิจสุนทร, สุปรีดิ์ (KKU Science Journal, 2016)
Thermoelectric materials are very interesting because they can directly convert thermal energy into electrical current. In this article, we have discussed one of thermoelectric oxide materials, i.e. BiCuSeO. This material has received a number of interests because of its stability at high temperature and the high efficiency in converting heat to electricity. This article has collected several research works related to this material including crystal structure, thermoelectric properties, and synthesis methods. The main focus is on improving thermoelectric properties of BiCuSeO. Several approaches have been attempted, for instance, doping Pb2+ or other elements in the BiCuSeO structure for enhancing phonon scattering, or increasing Cu vacancies in the BiCuSeO structure for creating more holes. The authors have compared the differences in each approach for enhancing thermoelectric properties. We have also, in the end, made suggestions for improving the thermoelectric efficiency of BiCuSeO.